A review on microalgae strains, cultivation, harvesting, biodiesel conversion and engine implementation. Issue 1 (2nd January 2021) - Duran, Sandeep Kumar; Kumar, Pramod; Sandhu, Sarbjot S
ABSTRACT: Microalgae are fast growing, accrue huge amounts of lipids (20–50% of dry weight), can survive in saline water and have great potential as a source of renewable fuel. The selection of a microalga strain and lipid extraction method vastly affects the economics and success of the algae-based oil industry. This study scrutinizes the selection of a microalga strain for maximum lipid yield, recent advances in cultivation systems including design and harvesting technologies, effectiveness of different lipid extraction methods with affected variable parameters, different technologies for converting algal oil to biodiesel, physical-chemical properties of algae biodiesel in comparison to biodiesel standards, and effects of microalgae biodiesel as a fuel on engine combustion, performance and emissions. The focus of this review paper is to conclude the research on cultivation, lipid extraction, conversion and engine applications by providing expedient information regarding efficient and commercially feasible technologies for the algae-based oil industry.